2016
DOI: 10.1186/s40425-016-0136-y
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer stem cells in patient pancreatic xenografts are sensitive to drozitumab, an agonistic antibody against DR5

Abstract: BackgroundTherapeutic resistance and tumor recurrence are two major hurdles in the treatment of pancreatic ductal adenocarcinoma. Recent findings suggest that both of these attributes are associated with a small subset of pancreatic tumor initiating cancer stem cells (CSCs). Here, we demonstrate that drozitumab, a human agonistic monoclonal antibody which binds the death receptor DR5, selectively eliminates CSCs, resulting in tumor growth inhibition and even regression of pancreatic tumors.MethodsTo examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Next, we used human pancreatic cancer PDX tumor models for alternative in vivo studies, since the PDX model is the most clinically relevant animal model and can present many of the histological features and heterogeneous treatment sensitivity/response of tumors found in patients [ 84 , 85 ]. It has been recently reported that pancreatic cancer PDXs retain active paracrine/Hedgehog signaling, and desmoplasia is active in PDX tumor mouse models [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, we used human pancreatic cancer PDX tumor models for alternative in vivo studies, since the PDX model is the most clinically relevant animal model and can present many of the histological features and heterogeneous treatment sensitivity/response of tumors found in patients [ 84 , 85 ]. It has been recently reported that pancreatic cancer PDXs retain active paracrine/Hedgehog signaling, and desmoplasia is active in PDX tumor mouse models [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…2a ), they were selected for the proceeding experiments. PaCa stem cell marker CD24 (Eng et al 2016 ) was detected and CD24 and EpCAM were sorted by flow cytometry. It was revealed that PANC-1 cells expressed CD44 (100%).…”
Section: Resultsmentioning
confidence: 99%
“…39 Another research demonstrated that drozitumab, a human agonistic monoclonal antibody binds with DR5 and selectively eliminates cancer stem cells in patient-derived pancreatic tumor xenografts (PDX) model, resulting in regression of PC and long-term tumor control. 40 Thus, the TRAIL death receptor expression in PC is an important target for the success of PC treatment.…”
Section: Discussionmentioning
confidence: 99%